How can African agriculture adapt to climate change: Integrated management of the Blue Nile Basin in Ethiopia under climate variability and climate change hydropower and irrigation modeling - Block, Paul J.; Strzepek, Kenneth M.; Rajagopalan, Balaji (International Food Policy Research Institute, 2008)
Ethiopia possesses abundant water resources and hydropower potential, yet less than 5 percent of irrigable land in the Blue Nile basin has been developed for food production, and more than 80 percent of Ethiopians lack access to electricity. Consequently, the Ethiopian government is pursuing plans to develop hydropower and irrigation along the Blue Nile River in an effort to tap into this underused potential. Although approximately 84 percent of the inflow to Lake Nasser at Aswan, Egypt, initiates from Ethiopia through the Blue Nile and Atbara Rivers, Ethiopia has limited rights to use these resources. Egypt and Sudan, through the Agreement of 1959, are allotted 55.5 and 18.5 billion cubic meters each year, respectively, with no allotment to Ethiopia. In 1998 the Nile Basin Initiative was created to stimulate cooperation among all countries in the Nile basin and work toward amicable alternatives and solutions for water resources benefits. This brief is based on a paper that analyzes potential hydropower generation and irrigation supply for four large-scale dams and reservoirs along the Blue Nile River within Ethiopia—Karadobi, Mabil, Mendaia, and Border—as proposed by the United States Bureau of Reclamation in 1964. The total installed hydropower capacity would be 5,570 megawatts of power, about 2.5 times the potential of the Aswan High Dam in Egypt. Irrigation associated with the Mendaia and Border reservoirs could expand by 250,000 hectares or 35 percent of the estimated total irrigable land in the Blue Nile basin. The challenges of implementation, however, are not inconsequential. The proposed reservoirs not only raise financing, investment, political, and institutional challenges, but may also require many years to fill, which will affect downstream flows depending on variable climate and climate change conditions. Using a model for hydropower and irrigation analysis, the paper explores dam implementation viability under various policy options.